Mixed epithelial and stromal tumour with extension to vesicoureteric junction - Arun Ramdas Menon; T.P. Rajeev; Nivedita Suresh; Suraj Hegde (Asian Journal of Urology)
Mixed epithelial and stromal tumour (MEST) is an uncommon renal tumour with a tendency to protrude into the collecting system. We present a 50-year-old woman with a renal tumour extending up to the vesicoureteric junction (VUJ) who was suspected to have an upper tract transitional cell carcinoma for which a nephroureterectomy was performed. Histopathologic examination revealed a MEST arising from the kidney and extending up to the VUJ. To the best of our knowledge, this is the first report of a renal MEST with extension to the VUJ. Keywords: Mixed epithelial and stromal tumour, Renal cell carcinoma, Renal tumour, Upper tract transitional cell carcinoma, Vesicoureteric junction